csee 3827 fundamentals of computer systems
play

CSEE 3827: Fundamentals of Computer Systems Lecture 3 January 28, - PowerPoint PPT Presentation

CSEE 3827: Fundamentals of Computer Systems Lecture 3 January 28, 2009 Martha Kim martha@cs.columbia.edu Agenda DeMorgans theorem Duals Standard forms DeMorgans Theorem Procedure for complementing expressions


  1. CSEE 3827: Fundamentals of Computer Systems Lecture 3 January 28, 2009 Martha Kim martha@cs.columbia.edu

  2. Agenda • DeMorgan’s theorem • Duals • Standard forms

  3. DeMorgan’s Theorem • Procedure for complementing expressions • Replace... • AND with OR, OR with AND • 1 with 0, 0 with 1 • X with X, X with X XY = X + Y X + Y = XY

  4. Prove DeMorgan’s Theorem XY = X + Y X Y XY X Y X + Y 0 0 0 0 0 1 0 1 1 0 1 0 1 1 1 1

  5. Prove DeMorgan’s Theorem XY = X + Y X Y XY X Y X + Y 1 1 0 0 0 0 1 1 0 1 0 1 1 1 1 0 1 0 0 0 1 1 1 1

  6. DeMorgan’s Practice F = ABC + ACD + BC

  7. DeMorgan’s Practice F = ABC + ACD + BC = (ABC)(ACD)(BC) = (ABCD)(B+C) = ABCD + ABCD = ABCD

  8. Duals

  9. Duals • A theorem about theorems • All boolean expressions have duals • Any theorem you can prove, you can also prove for its dual • To form a dual... • replace AND with OR, OR with AND • replace 1 with 0, 0 with 1

  10. What is the dual of this expression? X + Y = XY

  11. What is the dual of this expression? X + Y = XY dual XY = X + Y

  12. What are the complements of these expressions? X + Y = XY complement dual XY = X + Y complement

  13. What are the complements of these expressions? XY = X + Y X + Y = XY complement dual XY = X + Y X + Y = XY complement

  14. These are also the duals of one another. XY = X + Y X + Y = XY complement dual dual XY = X + Y X + Y = XY complement

  15. Can be used for gate manipulation. XY = X + Y X + Y = XY XY = X + Y X + Y = XY

  16. Boolean Algebra: Identities and Theorems OR AND NOT X+0 = X X1 = X (identity) X+1 = 1 X0 = 0 (null) X+X = X XX = X (idempotent) X+X = 1 XX = 0 (complementarity) X = X (involution) X+Y = Y+X XY = YX (commutativity) X+(Y+Z) = (X+Y)+Z X(YZ) = (XY)Z (associativity) X(Y+Z) = XY + XZ X+YZ = (X+Y)(X+Z) (distributive) X+Y = X Y XY = X + Y (DeMorgan’s theorem)

  17. Standard forms

  18. Standard Forms • There are many ways to express a boolean expression F = XYZ + XYZ + XZ = XY(Z + Z) + XZ = XY + XZ • It is useful to have a standard or canonical way • Derived from truth table • Generally not the simplest form

  19. Two principle standard forms • Sum-of-products (SOP) • Product-of-sums (POS)

  20. Sum-of-products form • sometimes also called disjunctive normal form (DNF) • sometimes also called a minterm expansion F = ABC + ABC + ABC + ABC + ABC A B C F F 0 0 0 1 0 0 0 1 1 0 0 1 0 1 0 0 1 1 0 1 1 0 0 1 0 1 0 1 1 0 1 1 0 0 1 1 1 1 0 1 F = ABC + ABC + ABC

  21. Sum-of-products form 2 (variables appear once in each minterm) A B C minterm F F 0 0 0 1 0 m0 ABC F = ABC + ABC + ABC + ABC + ABC 0 0 1 1 0 m1 ABC = m0 + m1 + m2 + m4 + m5 0 1 0 1 0 m2 ABC = ∑ m(1,0,2,4,5) 0 1 1 0 1 m3 ABC 1 0 0 1 0 m4 ABC F = ABC + ABC + ABC 1 0 1 1 0 m5 ABC = m3 + m6 + m7 1 1 0 0 1 m6 ABC = ∑ m(3,6,7) 1 1 1 0 1 m7 ABC

  22. Sum-of-products form 3 A B C F = ABC + ABC + ABC + ABC + ABC = m0 + m1 + m2 + m4 + m5 = ∑ m(1,0,2,4,5) F Standard form is not minimal form!

  23. Two principle standard forms • Sum-of-products (SOP) • Product-of-sums (POS)

  24. Product-of-sums form • sometimes also called conjunctive normal form (CNF) • sometimes also called a maxterm expansion F = (A+B+C) (A+B+C) (A+B+C) A B C F F 0 0 0 1 0 0 0 1 1 0 0 1 0 1 0 0 1 1 0 1 1 0 0 1 0 1 0 1 1 0 1 1 0 0 1 1 1 1 0 1

  25. Product-of-sums form • sometimes also called conjunctive normal form (CNF) • sometimes also called a maxterm expansion F = (A+B+C) (A+B+C) (A+B+C) A B C F F 0 0 0 1 0 0 0 1 1 0 0 1 0 1 0 0 1 1 0 1 1 0 0 1 0 1 0 1 1 0 1 1 0 0 1 1 1 1 0 1 F = (A+B+C) (A+B+C) (A+B+C) (A+B+C) (A+B+C)

  26. Product-of-sums form 2 A B C maxterm F F 0 0 0 1 0 M0 A+B+C F = (A + B + C) (A + B + C) (A + B + C) 0 0 1 1 0 M1 A+B+C = (M3)(M6)(M7) 0 1 0 1 0 M2 A+B+C = ∏ M(3,6,7) 0 1 1 0 1 M3 A+B+C 1 0 0 1 0 M4 A+B+C F = (A+B+C) (A+B+C) (A+B+C) (A+B+C) (A+B+C) 1 0 1 1 0 M5 A+B+C = (M0)(M1)(M2)(M4)(M5) 1 1 0 0 1 M6 A+B+C = ∏ M(0,1,2,4,5) 1 1 1 0 1 M7 A+B+C

  27. Summary of SOP and POS F F Sum of products ∑ m(F = 1) ∑ m(F = 0) (SOP) Product of sums ∏ M(F = 0) ∏ M(F = 1) (POS)

  28. Standard Form Example A B C F F 0 0 0 0 1 0 0 1 1 0 0 1 0 0 1 0 1 1 1 0 1 0 0 0 1 1 0 1 1 0 1 1 0 1 0 1 1 1 0 1 F F Sum of products (SOP) Product of sums (POS)

  29. Standard Form Example A B C F F 0 0 0 0 1 0 0 1 1 0 0 1 0 0 1 0 1 1 1 0 1 0 0 0 1 1 0 1 1 0 1 1 0 1 0 1 1 1 0 1 F F ∑ m(1,3,5,6) ∑ m(0,2,4,7) Sum of products (SOP) ∏ M(0,2,4,7) ∏ M(1,3,5,6) Product of sums (POS)

  30. Converting between canonical forms F F Sum of products ∑ m(F = 1) ∑ m(F = 0) (SOP) Product of sums ∏ M(F = 0) ∏ M(F = 1) (POS) DeMorgans

  31. Next class: systematic minimization

Download Presentation
Download Policy: The content available on the website is offered to you 'AS IS' for your personal information and use only. It cannot be commercialized, licensed, or distributed on other websites without prior consent from the author. To download a presentation, simply click this link. If you encounter any difficulties during the download process, it's possible that the publisher has removed the file from their server.

Recommend


More recommend